VEGF-Mediated Proliferation of Human Adipose Tissue-Derived Stem Cells - Chen, Guangfeng (Public Library of Science, 2013)
Human adipose tissue-derived stem cells (ADSCs) are an attractive multipotent stem cell source with therapeutic applicability across diverse fields for the repair and regeneration of acute and chronically damaged tissues. In recent years, there has been increasing interest in ADSC for tissue engineering applications. However, the mechanisms underlying the regulation of ADSC proliferation are not fully understood. Here we show that 47 transcripts are up-regulated while 23 are down-regulated in ADSC compared to terminally differentiated cells based on global mRNA profiling and microRNA profiling. Among the up-regulated genes, the expression of vascular endothelial growth factor (VEGF) is fine-tuned by miR-199a-5p. Further investigation indicates that VEGF accelerates ADSC proliferation whereas the multipotency of ADSC remains stable in terms of adipogenic, chondrogenic and osteogenic potentials after VEGF treatment, suggesting that VEGF may serve as an excellent supplement for accelerating ADSC proliferation during in vitro expansion.